End-to-End Delay and Energy Efficient Routing Protocol for Underwater Wireless Sensor Networks - Ali, T. (Kluwer Academic Publishers, 2014)
Providing better communication and maximising the communication performance in a Underwater Wireless Sensor Network (UWSN) is always challenging due to the volatile characteristics of the underwater environment. Radio signals cannot properly propagate underwater, so there is a need for acoustic technology that can support better data rates and reliable underwater wireless communications. Node mobility, 3-D spaces and horizontal communication links are some critical challenges to the researcher in designing new routing protocols for UWSNs. In this paper, we have proposed a novel routing protocol called Layer by layer Angle-Based Flooding (L2-ABF) to address the issues of continuous node movements, end-to-end delays and energy consumption. In L2-ABF, every node can calculate its flooding angle to forward data packets toward the sinks without using any explicit configuration or location information. The simulation results show that L2-ABF has some advantages over some existing flooding-based techniques and also can easily manage quick routing changes where node movements are frequent. Â© 2014, Springer Science+Business Media New York.